The optimal concentration of bone morphogenic protein 2 as a signal for mineralized tissue engineering using stem cells from human deciduous teeth - Saaid Al Shehadat; Wan Zaripah Wan Bakar; Nurul Asma Abdullah; Sam'an Malik Masudi; Rumaizi Bin Shaari (2015)
Objective: To determine the optimal concentration of BMP2 to be used with primer stem cells from human deciduous teeth (deciduous teeth stem cells |DTSCs|) for mineralized tissue engineering. Design: Experimental in vitro study. Materials and Methods: DTSCs were isolated and characterized by flow cytometry using mesenchymal stem cells marker; CD105 and CD166. Different concentrations of BMP2 (0, 25, 50, 100 and 200 ng/ml) were added to the cells and incubated for 14 days. MTT assay was performed to detect the viability of the cells treated with the various concentrations of BMP2 following the first 3 days treatment. Alkaline phosphatase (ALP) assay was performed to detect any significant differences in the activity levels of the extracellular ALP secretion for 14 days. Results: The different concentrations of BMP2 showed no effect on the cell viability on the first 3 days. BIY1P2 was able to increase the activity of extracellular ALP in a-dose dependent manner. There were significant differences in the ALP activity after treatments with 25 ng/ml and 50 ng/ml BMP2. However, there were no significant differences in the ALP activity when comparison made to each concentration except between 25 ng/ml and 50 ng/ml. Conclusion: BIV1P2 with concentration of 50 ng/ml is the concentration of choice in regeneration of mineralized tissue engineering using DTSCs.